Judiciary in the Serbian Constitution of 2006 and a critical review of draft amendments - Stanković Marko (Anali Pravnog Fakulteta u Beogradu)
This article analyzes the position of judiciary in the Constitution of the Republic of Serbia. Legal norms on the organization of judiciary are one of the most important segments of constitutional matter, having in mind that for the functioning of democracy it is important to ensure complete independence of the judiciary from so-called 'political authorities' - legislative and executive. The independence of the judiciary can only be ensured by the constitution. However, the Serbian Constitution of 2006 has taken a different stand on this part of constitutional matter, giving the legislator a wide authority to regulate substantive issues relating to the judiciary (election and dismissal of judges), which largely subordinates judicial power to the legislative. First, the constitutional norms on judiciary will be analyzed in this paper. The Serbian Constitution contains five key issues related to the independence of judiciary. Further analysis will include proposed amendments to the Constitution. Ministry of Justice's Working Version of the Draft Amendments to the Constitution has not adequately solved any of five problems. Finally, useful conclusions about the position of the judiciary in the Republic of Serbia will be drawn. .